Ayurvedic Management of Subclinical Hypothyroidism Vis-À-Vis Kaphavrita Udanavata – A Pilot Study - Vedavati; Belavadi, Santosh N (International Research Journal of Ayurveda & Yoga, 2023)
Hypothyroidism is a common medical condition that affects the thyroid gland, which is located in the neck and is responsible for producing hormones that regulate metabolism. When the thyroid gland does not produce enough of these hormones. It can lead to a range of symptoms and health problems such as reduced appetite, dry skin, irregular menstrual cycle, cold intolerance, hoarseness of voice, weight gain, and fatigue. Diagnosis of hypothyroidism typically involves blood tests to measure the levels of thyroid hormones and thyroid stimulating hormone. Moreover, conservative treatment involves the consumption of synthetic thyroid hormones to replace the inadequacy of thyroid hormones on daily basis. In Ayurveda, we can correlate this condition with the Kaphavrita Udanavata based on symptoms. A pilot study has been conducted to observe the efficacy of Panchatiktha Ghrita Guggulu in managing subclinical hypothyroidism vis-à-vis Kaphavrita Udanavata. Hence, this piece of work is an effort to add value to the Ayurvedic Treatment Modalities by showing that hypothyroidism can be managed by Ayurvedic intervention alone.